Improving masked communication: the case for transparent masks - McCrackin, Sarah D.; Ristic, Jelena (Frontiers in Communication, 2024)
Clear and compassionate communication is tantamount to quality of care and patient wellbeing. Yet, much of communication in healthcare occurs with lower faces visually hidden behind opaque face masks. Visual occlusion of the face by masks impairs both verbal and nonverbal communication, including recognition of basic emotions, perceptions of trustworthiness, emotional understanding, and empathic responding. This piece presents a brief overview of the new Covid-19 inspired literature which shows that visual face occlusion creates significant communication barriers which can be reduced by wearing transparent instead of opaque masks.